PERADILAN AGAMA DALAM SISTEM HUKUM INDONESIA - Martius, A. Havizh (DIKTUM: Jurnal Syariah dan Hukum, 2016)
The political influence of the law against the existence and position of Religious Courts in Indonesia marked by legal products on which the existence and position of the Religious Courts. The philosophical basis of the existence of the Religious Courts in Indonesia are the values of Pancasila embraced by the Indonesian people, especially the first principle "Almighty God" that animates the other precepts. While the sociological basis of the existence of the Religious Court based on Islamic law is a reflection of the norms of Indonesia Muslim majority. Islamic law is law who lived in Indonesia since the Islamic community began to flourish in the country. As for the legal basis which is the constitutional basis for the existence of Religious Courts in Indonesia is Pancasila, the Presidential Decree July 5, 1959, and 1945.